Expansion power system transmission using ant colony optimization: article / Izzataswad Ibrahim - Ibrahim, Izzataswad (2015)
This paper presents an application of ant colony optimization (ACO) to optimization the expansion transmission in power system. The main objective this proposal to find the lowest investment total cost transmission network. A 24 bus reliability test using in transmission expansion analysis, the results show that the algorithm is capable to deliver good solutions for relatively large systems[1]. Ant colony optimization represent the behaviour of ant, when ant go outside their nest to find food, ants will leave pheromone to make pheromone such as track to came back to nest[2]. However ant will more interested at track have high pheromone intensity, high pheromone happen when too many ants through that [3]. Therefore high pheromone occurs at short distance trail.